2015
DOI: 10.1186/s40064-015-1145-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of selected metals in leaves of Cannabis sativa L. cultivated in Ethiopia

Abstract: BackgroundCannabis sativa L. is one of the illicit drug bearing plants. Cannabis products are the most widely trafficked drugs worldwide. The highest levels of cannabis production in the world take place in the African continent. A small volume of cannabis is produced in rural areas of Ethiopia, of which a small portion is exported to neighboring countries and the majority is consumed at home. The literature survey revealed that there is no report on the metal contents in cannabis cultivated in Ethiopia. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
2
12
1
Order By: Relevance
“…Dried leaves were then crushed using an electric grinder and sieved to obtain fine powder. Powder was kept under clean and dry polyethylene bags [42]. The extraction of cannabinoids and terpenes was then carried out, according to the following extraction procedure.…”
Section: Plant Collection and Extraction Of Phytochemicalsmentioning
confidence: 99%
“…Dried leaves were then crushed using an electric grinder and sieved to obtain fine powder. Powder was kept under clean and dry polyethylene bags [42]. The extraction of cannabinoids and terpenes was then carried out, according to the following extraction procedure.…”
Section: Plant Collection and Extraction Of Phytochemicalsmentioning
confidence: 99%
“…Several studies have also been reported in the literature on determinations of the levels of heavy metals in the raw and processed tobacco leaves (Kaličanin and Velimirović 2012 ; Eneji et al 2013 ; Ajab et al 2014 ) in the different parts of the world using different techniques (Saldivar et al 1991 ; Health Canada 1999 ; Stojanovic et al 2004 ; Angelova et al 2004 ; Zhang et al 2005 ; Nnorom et al 2005 ). Some studies have also been carried out in Ethiopia on the levels of essential and non-essential metals in a psychoactive khat leaves (Atlabachew et al 2010 , 2011 ) as well as in cannabis leaves (Zerihun et al 2015 ). A few studies have also been carried out on the levels of nicotine in Ethiopian tobacco leaves (Geto et al 2012 ; Kassa et al 2013 ; Tassew and Chandravanshi 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zn was with the highest concentration among trace metals [27]. The results indicated that the content of Pb and Cd exceeded the permissible amount for medicinal plants which form the raw materials for the finished products set by World Health Organization (WHO) [27].…”
Section: Cannabismentioning
confidence: 85%
“…The levels of metals determined (μg/g dry weight) were in the ranges Ca (657-1,511), Zn (321-380), Ni (124-172), Cu (122-176), Cd (3-10), Pb (8-10), and Cr (4)(5)(6)(7)(8). Zn was with the highest concentration among trace metals [27]. The results indicated that the content of Pb and Cd exceeded the permissible amount for medicinal plants which form the raw materials for the finished products set by World Health Organization (WHO) [27].…”
Section: Cannabismentioning
confidence: 99%
See 1 more Smart Citation